Measurement Invariance of the Questionnaire on the Internal Stigma of Internet Surfing Among Sino-Australian Undergraduates - Luo, Jie; Ge, Ying; Hao, Ji-chun; Wilkinson, Ross B.; Wenger, Jay L. (Frontiers in Psychiatry, 2022)
Background: The stigma of internet surfing is a relatively new area of study arising from the popularity of the internet. The Questionnaire on the Internal Stigma of Internet Surfing-9 (QISIS-9) was developed for the Chinese culture, so its suitability for use in other cultural contexts is uncertain. This paper examines the measurement invariance of the QISIS-9 among Sino-Australian undergraduates to verify the cross-cultural measurement invariance of QISIS-9 and promote cross-cultural (nationality) research regarding the internal stigma of internet surfing. Methods: The Internal Stigma of Internet Surfing-9 (QISIS-9) was used to assess 200 Chinese undergraduates (50% female, Mage=19.78) and 204 Australian undergraduates (76% female, Mage=21.10), respectively. Results: A confirmatory factor analysis (CFA) indicated that the single-factor model of QISIS-9 is acceptable with both Chinese and Australian undergraduates. However, the factor loading of Item 9, to which a reverse score is assigned, is not ideal for both samples. Thus, the item should be deleted. According to a multigroup confirmatory factor analysis (MCFA), QISIS-8, the revised version of QISIS-9, meets the strict measurement invariance among the Chinese and Australian participants. The QISIS-8 demonstrated appropriate internal consistency in the scores for both the Chinese and Australian undergraduates. Conclusion: The new QISIS-8 can effectively assess the internal stigma of internet surfing among Chinese and Australian undergraduates, and it provides a frame of reference for further cross-cultural (border) comparisons.